Tabernanthalog and ibogainalog inhibit the α7 and α9α10 nicotinic acetylcholine receptors via different mechanisms and with higher potency than the GABAA receptor and CaV2.2 channel - Tae, Han Shen (2024)
In this study, we have investigated the pharmacological activity and structural interaction of two novel psychoplastogens, tabernanthalog (TBG) and ibogainalog (IBG) at heterologously-expressed rat (r) and human (h) nicotinic acetylcholine receptors (nAChRs), the rα1β2γ2L γ-aminobutyric acid type A receptor (GABAAR), and the human voltage-gated N-type calcium channel (CaV2.2 channel). Both compounds inhibited the nAChRs with the following receptor selectivity: α9α10 > α7 > α3β2 ≅ α3β4, indicating that β2/β4 subunits are relatively less important for their activity. The potencies of TBG and IBG were comparable at hα7 and hα9α10 subtypes, and comparable to their rat counterparts. TBG- and IBG-induced inhibition of rα7 was ACh concentration-independent and voltage-dependent, whereas rα9α10 inhibition was ACh concentration-dependent and voltage-independent, suggesting that they interact with the α7 ion channel pore and α9α10 orthosteric ligand binding site, respectively. These results were supported by molecular docking studies showing that at the α7 model TBG forms stable interactions with luminal rings at 9′, 13′, and 16′, whereas IBG mostly interacts with the extracellular-transmembrane junction. In the α9α10 model, however, these compounds interacted with several residues from the principal (+) and complementary (–) sides in the transmitter binding site. Ibogaminalog (DM506) also interacted with a non-luminal site at α7, and one α9α10 orthosteric site. TBG and IBG inhibited the GABAAR and CaV2.2 channels with 10 to 30-fold lower potencies. In sum, we show that TBG and IBG inhibit the α7 and α9α10 nAChRs by noncompetitive and competitive mechanisms, respectively, and with higher potency than the GABAAR and CaV2.2 channel.